(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Artificial intelligence is slowly becoming a general-purpose technology applicable in all areas of social life. Social existence in a certain territory is determined by the connection of citizens and state institutions, that is, public exposure and work in favor of the general interest of citizens through various branches of the state or services known as the public sector. We are thus witnessing the penetration or gradual introduction of artificial intelligence in the public sector or public administration with the aim of easier servicing and improvement of the benefits that the state should provide to citizens. The benefits are reflected in the realization of certain rights of citizens as well as in the improvement of economic activities in which citizens and society are very interested. In the paper, we analyze the introduction and use of certain artificial intelligence systems in the public sector, i.e. in its individual parts, we look at its disjointed elements that vary from country to country, attempts to establish common terms and patterns, and we investigate sensitive and critical areas of public services based on the taxonomy EU. In this context, the connection between digitization and the creation of e administration, which potentially includes artificial intelligence systems, is interesting, requiring capacity building and the acquisition of new skills and knowledge for public administration employees. The emphasis in the paper is on the legal framework for their use provided by the EU Regulation on artificial intelligence, especially on the categorization of certain artificial intelligence systems into prohibited and high-risk systems that could be used in the public sector. A special part of the paper is devoted to the assessment of the anticipated use of artificial intelligence systems in the public sector in the Republic of Serbia by establishing a legal framework with soft law norms such as the Strategy for the Development of Artificial Intelligence in the Republic of Serbia for the period 2020-2025. which was adopted in 2019 and the Ethical guidelines for the development, implementation and use of reliable and responsible Artificial Intelligence from 2023.